More Generals in Gray - Allardice, Bruce S. (Book collections on Project MUSE., 2006)
In this masterpiece of research, a splendid supplement to Ezra J. Warner's Generals in Gray, Bruce S. Allardice brings to light a neglected class of officers: the Confederacy's ""other"" generals-men who attained their rank outside the usual avenue of appointment by President Jefferson Davis and who had been virtually forgotten as a consequence. Explaining that the process of becoming a general was fraught with politics, lobbying, intrigue, accident, mismanagement, and chance, Allardice identifies six main categories of legitimate claimants to the rank of Confederate General-two more than hist.